APPLICATION PORTFOLIO STMIK JAKARTA CAMPUS STI & K USING MACROMEDIA FLASH 8.0 - Yoestian Abdullah; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Scientific writing is about a Portfolio Application Campus STMIK STI & K. Jakarta To Create Multimedia Animation. This application was  created to provide information to users in order to simplify the familiar campus STMIK STI & K. Jakarta            In scientific writing, Multimedia Applications To Create Animations author using Macromedia Flash 8.0 which will support the presentation of  learning methods in these applications include the use of writing and moving images. thus can be expected to attract more users in identifying campus STMIK STI & K. Jakarta